Tradução: Uma Transparência do Tradutor - Tagnin, Stella E. O.; Camargo, Sidney (TradTerm, 1994)
The authors apply Juliane House's model (2) for translation quality assessment to a self-help text and its Brazilian translation. The model claims that a translation text should be semantically and pragmatically equivalent to the source-text. This equivalence is assured if both texts are shown to have the same function. Through the application of the model it was possible to determine the interpersonal function of the source-text, assess to what extent the translation expresses the same function and even reveal quite precise personal traits of the translator.